(Un)Making home at the borderlands of the rural and the urban: Chinese migrant women's narratives. Issue 2 (2nd April 2020) - Li, Zhou; Chen, Yea-Wen
Abstract : This study examines the discourses collected in interviews with second-generation Chinese rural migrant women in Chongqing to unpack how they make sense of home. Guided by Blunt and Dowling's (2006 ) critical geography of home and Anzaldúa's concept of borderlands, we interpret three overlapping themes: (a) constantly (re)making "home" that is neither here nor there; (b) bordering in-between aging parents and young child(ren); (c) social and political changes (un)making home in migration. Our findings endorse approaching "home" as a verb to better capture complex experiences with homing at borderlands.